Encroachment on green spaces in the city of Najaf (1958-2009 AD) A field study based on master plans for cities (Journal of the College of Basic Education, 2022)
The idea of ​​this research is to show the concept of encroachment in general and the phenomenon of encroachment on green spaces in particular through the basic design of the city and knowledge of the laws and decisions in this regard, and then try to come up with specific proposals to reduce this problem, and that this research relied on literature and research that dealt with such a phenomenon In addition to adopting field observations by roaming in places where such transgression occurred and the field study conducted by the research, and then coming up with conclusions and recommendations in this regard.